(untitled) (International Journal of Physiotherapy, 2014)
Background: Flexibility is important in prevention of injury, muscular and postural imbalance more over the Hamstring flexibility has a lion share in sports performances and preventing DOMS. Stretching procedures increases the ROM by embarking on biomechanics and Neurologic and molecular mechanics. Hamstrings, the two joint muscle plays a crucial role in two joints integrity and also spine as they are in closed kinematic chain. The hamstring muscles represent the primary flexors of Knee. Hamstrings tightness results in Limits Knee extension when hip is flexed, Posterior Pelvic tilt, and flatten the lumbar spine. Methods: The subjects selected randomly and divided into two groups (Experimental group and control group).30 samples in One group applied with Static Stretch once a day for 3 repetitions 5 days a week for six weeks and 30 samples in other group applied with Hold relax technique once a day for 4 repetitions 5 days a week for six weeks. The knee joint range of motion was measured at the end of every week with Universal goniometer. Results: By comparing the means of Group – I, given Static Stretch and Group – II, given Hold relax Technique for six weeks implied that there is improvement of flexibility in Group – II and the ‘P’ value < 0.01 shows the difference is highly significant. Conclusion: This study concludes that the hold relax Technique method has proved to be better technique then the static stretch for improving hamstring flexibility. Keywords: Static stretch, Hold relax, Hamstring flexibility.